In Vitro and In Vivo Anti Hyperglycemic Evaluation of Sterculia quadrifida Bark through The Inhibition of Alpha Glucosidase - Jeffry Julianus; Maria Dewi Puspitasari Tirtaningtyas Gunawan-Puteri; Radhita Tyastu Puteri Wiwengku; Agustina Setiawati; Phebe Hendra (Sanata Dharma University, 2023)
Data from the International Diabetes Federation revealed annual increases in the prevalence of diabetes mellitus, which require special attention. Implementation of the ‘back to nature’ trend presents opportunities to overcome this problem. As a medicinal plant, Faloak is widely used by people in Nusa Tenggara Timur, Indonesia. This study aimed to evaluate in vivo and in vitro anti-hyperglycemic activity of the bark of Sterculia quadrifida, known as Faloak. In vivo evaluation used sucrose-induced male mice. Measurements of glucose level employed a glucometer and data were analyzed statistically. Demonstrating anti-hyperglycemic activity of the bark of Faloak decoct, results showed doses 1.67 and 3.3 g/kg BW reduced glucose levels by 62.2% and 56.9%, respectively. In vitro examination of Faloak decoct at various concentrations used alpha glucosidase (sucrose) enzymatic reaction. Results of in vitro examinations demonstrated of Faloak bark decoct inhibited alpha glucosidase (sucrose) activity by 42.09 ± 4.39%. Further testing on humans is needed to confirm these findings.